Social Interaction and Its Relationship with the Counseling Communication Skills for Educational Counselors - Mahdi, Areej Hazim (International Journal of Psychosocial Rehabilitation, 2020)
This research aims are identifying as follows: • The social interaction for educational • The communication counseling skills for educational • The statistical in social interaction according to the gender(male, female) • The statistical Differences in communication counseling skills according to the gender(male, female) • The correlation between social interaction and counseling skills according to the gender(male, female) The Sample of research consists of (150) counselors (male, female),The researcher Adopted a social interaction scale based on belles Theory in(1950)and a scale of counseling communication skill was built according to the (1988) Honey definition The researcher used (T.test) for independent samples (T.test) for one sample ,person correlation coefficient ,Alpha Cronbach formula as statistical tools , The researcher in visit gated for psycho metric characteristics such as face validity and Reliability by Alpha Cronbach .The researcher arrived to many results then sets many recommendation and suggestions.